NOTAS PARA LA HISTORIA DEL CENTENARIO DEL BALONCESTO ESPAÑOL. UN DEPORTE ESCOLAR Y POPULAR PARA AMBOS SEXOS (1897-1938) [Notes for the history of the Spanish basketball centenary. A school and popular sport for both sexes (1897-1938)] - Xavier Torrebadella-Flix; Jordi Ticó Camí (Federación Extremeña de Balonmano; University of Extremadura, 2015)
El baloncesto se introdujo en España como un contenido expreso para atender la educación física escolar. Las ventajas que pedagogos, profesores de educación física, higienistas y militares vieron en este deporte tenían como miras el ser una práctica de equipo con un alto valor cooperativo, poco violento, de ejercicio moderado y completo y, por tanto, higiénico y mejor dispuesto para ambos sexos. Ello hizo que como deporte se alejara de la emergencia aristocrática o burguesa de otros deportes de moda y, que también, se presentará como una alternativa al popular fútbol, en el momento en que adquiría su máxima plenitud como deporte de espectáculo y de masas. Abstract Basketball was introduced in Spanish curricula as a means to promote physical education. Among the benefits identified in this sport by pedagogues, physical education teachers, hygienists and the military highlight those related with the promotion of teamwork competences, high level of cooperation, non-violent, moderate exercise and therefore with strong values for hygiene and available to both genders. These basketball potential educative benefits presented this sport as a valuable alternative to football, at a time that football became a sport of the masses and available to everyone.